Experimental study on strength of cracked concrete column repaired by jacketing method - Muhammad Zulhilmi, Ali (2012)
This study is to investigate the strength, crack pattern, and failure pattern in crack concrete column repair by jacketing method. The scope of this research is limited to overloading load and the sample is made using concrete G25. The reinforcement concrete has been design and analyse according to BS5950 with T12 for main bar and R6 for shear link. Two samples with colmnn size of 125 mm x 125 mm x 1500 mm was prepared for repair method, and the structural test is carried out after reach 28 days strength using strong floor machine with rate 0.55 mm per minute. The samples were preloaded under axial compression to its ultimate load; repair using jacketing method in grouting mortar and then retested to failure. The result show that the original maximum load indicate highest value compare to maximum load after repaired by jacketing method. Diagonal crack is observed in original colmnn and transverse crack is observed in colmnn after repaired. As conclusion, the jacketing method used in this study failed to restore the strength of cracked concrete colmnn.